Eeyore: a novel mouse model of hereditary deafness. - Kerry A Miller; Louise H Williams; Hans-Henrik M Dahl; Shehnaaz S M Manji (PLoS ONE, 2013)
Animal models that recapitulate human disease are proving to be an invaluable tool in the identification of novel disease-associated genes. These models can improve our understanding of the complex genetic mechanisms involved in disease and provide a basis to guide therapeutic strategies to combat these conditions. We have identified a novel mouse model of non-syndromic sensorineural hearing loss with linkage to a region on chromosome 18. Eeyore mutant mice have early onset progressive hearing impairment and show abnormal structure of the sensory epithelium from as early as 4 weeks of age. Ultrastructural and histological analyses show irregular hair cell structure and degeneration of the sensory hair bundles in the cochlea. The identification of new genes involved in hearing is central to understanding the complex genetic pathways involved in the hearing process and the loci at which these pathways are interrupted in people with a genetic hearing loss. We therefore discuss possible candidate genes within the linkage region identified in eeyore that may underlie the deafness phenotype in these mice. Eeyore provides a new model of hereditary sensorineural deafness and will be an important tool in the search for novel deafness genes.